2005
DOI: 10.1016/j.jasms.2005.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometric detection of self-assembly of a crown ether complex directed by π-stacking interactions

Abstract: The self-assembly of ligand-metal-ligand sandwich complexes involving a novel quinoxalinecontaining crown ether, 1, was studied by electrospray ionization mass spectrometry (ESI-MS). Donor-acceptor -stacking interactions between the electron-poor quinoxaline group of 1 and electron-rich benzene groups from benzo-or dibenzo-18-crown-6 were found to significantly enhance the formation of mixed-ligand sandwich complexes with a free energy gain of up to 17 kJ/mol relative to sandwich formation involving macrocycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 49 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…The results of ESI-MS analysis of the host-guest complexes (including those involving macrocycles) correlate well with the measurements of the equilibriums in solution [7,18]. It has been clearly demonstrated by Brodbelt and coworkers that the host-guest complexes, which have similar conformations and structural features, such as a simple crown ether binding to two different alkali metal ions, have similar electrospray ionization efficiencies [19].…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The results of ESI-MS analysis of the host-guest complexes (including those involving macrocycles) correlate well with the measurements of the equilibriums in solution [7,18]. It has been clearly demonstrated by Brodbelt and coworkers that the host-guest complexes, which have similar conformations and structural features, such as a simple crown ether binding to two different alkali metal ions, have similar electrospray ionization efficiencies [19].…”
Section: Resultssupporting
confidence: 72%
“…As clearly justified by the authors [7], the concentrations of the homo-ligand complexes ( ) can be replaced by respective peak intensities in the ESI mass spectra obtained. Further, in the same paper the Gibbs free-energy was calculated as ⌬G ϭ ϪRT lnK, and it was concluded that "large positive ⌬G values signify that the homo-ligand complexes are favored, near-zero values mean that the homo-ligand and mixed-ligand complexes are equally favored, and large negative values reflect a strong preference for formation of mixed-ligand sandwich complexes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been found that cation-interactions are of crucial importance for formation of complexes between dibenzo-24-crown-8 and tetramethylammonium cation [8]. Donoracceptor -stacking interactions have been established to significantly enhance the formation of mixed-ligand sandwich complexes formed by crown ethers [9]. Crown ethers having aromatic sidearms exhibited cation-interactions between K ϩ and a benzene ring [10].…”
mentioning
confidence: 99%